PENGARUH FREKUENSI DAN WAKTU PENCUCIAN BERBANTU ULTRASONIK MENGGUNAKAN ISOPROPANOL TERHADAP KADAR GLUKOMANAN DAN VISKOSITAS TEPUNG PORANG (Amorphophallus oncophyllus) - Lucia Hermawati Rahayu; Dyah Hesti Wardhani; Abdullah Abdullah (Universitas Diponegoro, 2014)
Abstract Konjac (Amorphophallus oncophillus) contains a high economic value of soluble fiber glucomannan. Most of Indonesia konjac flour is exported in low (glucomannan content <65) hence sell in cheap price. Quality of glucomannan could be improved by removing impurities such as starch and cellulose. Application of ultrasonic-assisted extraction (leaching) of non glucomannan compound is an effective method to purify the konjac flour. The purpose of this study was to study the effect of ultrasonic waves frequency and leaching time of ultrasonic-assisted extraction method using aqueous isopropanol on glucomannan purification. The leaching conducted two frequencies (20 and 40 kHz) and various extraction time (5, 10, 15, 20, 25 minutes). The results showed that the best condition of glucomannan purification was achieved at 20 kHz for 10 minutes. In this conditon, glucomannan content , viscosity and yield were 76.1%, 12,800 cPs, and 96.1%, respectively. Keywords: konjac (Amorphophallus oncophillus), glucomannan, ultrasonic-assisted extraction, isopropanol